Intestinal Macrophages Balance Inflammatory Expression Profiles via Vitamin A and Dectin-1-Mediated Signaling - Erkelens, Martje N.; Goverse, Gera; Konijn, Tanja; Molenaar, Rosalie; Beijer, Marieke R.; Van den Bossche, Jan; de Goede, Kyra E.; Verberk, Sanne G. S.; de Jonge, Wouter J.; den Haan, Joke M. M.; Mebius, Reina E. (Frontiers in Immunology, 2020)
Tissue resident intestinal macrophages are known to exhibit an anti-inflammatory phenotype and produce little pro-inflammatory cytokines upon TLR ligation, allowing symbiotic co-existence with the intestinal microbiota. However, upon acute events such as epithelial damage and concomitant influx of microbes, these macrophages must be able to quickly mount a pro-inflammatory response while more inflammatory macrophages are recruited from the blood stream simultaneously. Here, we show that dietary intake of vitamin A is required for the maintenance of the anti-inflammatory state of tissue resident intestinal macrophages. Interestingly, these anti-inflammatory macrophages were characterized by high levels of Dectin-1 expression. We show that Dectin-1 expression is enhanced by the vitamin A metabolite retinoic acid and our data suggests that Dectin-1 triggering might provide a switch to induce a rapid production of pro-inflammatory cytokines. In addition, Dectin-1 stimulation resulted in an altered metabolic profile which is linked to a pro-inflammatory response. Together, our data suggests that presence of vitamin A in the small intestine enhances an anti-inflammatory phenotype as well as Dectin-1 expression by macrophages and that this anti-inflammatory phenotype can rapidly convert towards a pro-inflammatory state upon Dectin-1 signaling.